PENGARUH INISIASI MENYUSU DINI TERHADAP KECEPATAN INVOLUSI UTERI PADA IBU POST PARTUM - Wiyati, Nining; Eni, Marciana; Hastuti, Sari (Jurnal Kesehatan Ibu dan Anak, 2012)
Maternal Mortality Rate in Indonesia in 2009 were 226/100.000 live births, one of which is caused by bleeding. The cause of bleeding one of which is sub-involution of the uterus. Early initiation of breastfeeding is one of the factors that can accelerate the involution of the uterus as it stimulates oxytocin which causes the uterus to contraction. Objective: To determine the effect of on Early initiation of breastfeeding pace maternal postpartum uterine involution in Sleman, Tutik Purwani clinic in 2012. The study design control time series design. Research location Tutik Purwani clinic Sleman. Consecutive sampling with sampling. Subjects were followed during maternal postpartum of the first 2 hours until the fundus no longer palpable. Number of samples 32 people treatment group Early initiation of breastfeeding and 32 control group (no Early initiation of breastfeeding). Hypothesis testing using an independent t-test Results: Speed corresponding uterine involution (high uterine fundus not palpable = 10 days postpartum), the Early initiation a breastfeeding as much as96.87%, while the number 56.25% no Early initiation of breastfeeding. Mean high uterine fundus postpartum mothers with Early initiation of breastfeeding is not palpable, day 7 (mean = 6.78), whereas postpartum mothers did not mean no palpable Early initiation of breastfeeding, high uterine fundus day 11 (mean = 11 .03). There is the influence of the velocity Early initiation of breastfeeding maternal postpartum uterine involution (t count> t table (7.07> 2.021) and the p-value <0.05 (p-value = 0.000) with a confidence interval (CI 95%). There effect Early initiation of breastfeeding, on uterine involution speed.